Ag‐CuO Nanocomposites: Surface‐Enhanced Raman Scattering Substrate and Photocatalytic Performance. Issue 7 (31st May 2019) - Ye, Fen; Ju, Suxiao; Liu, Yuanjun; Jiang, Yuerong; Chen, Hui; Ge, Lihong; Yan, Chao; Yuan, Aihua
Abstract: Porous Ag‐CuO nanocomposites are prepared with a photochemical reduction method. The obtained Ag‐CuO nanocomposites have bifunctions; they can not only be used as surface‐enhanced Raman scattering (SERS) substrates, providing an enhancement factor of 3.86 × 10 7 toward rhodamine 6G (R6G) and 7.08 × 10 7 toward p ‐aminothiophenol, but also can be used as an effective photocatalyst to degrade dyes, including R6G with H2 O2 under light irradiation. For example, the Ag‐CuO nanocomposite can degrade 96.7% of R6G within 2 h. It is believed that the porous microstructure provides more "hot‐spots" for SERS and active sites for photocatalytic process, inducing excellent performance. Due to the bifunctions, reuse of the Ag‐CuO SERS substrate is demonstrated with the assistance of light irradiation cleaning process. After eight reuse cycles, the enhancement factor of the substrate to R6G is still retained at 1.45×10 5 . Abstract : Porous Ag‐CuO nanocomposites are prepared, which can not only be used as surface‐enhanced Raman scattering substrates providing enhancement factor of 10 7 toward rhodamine 6G and p ‐aminothiophenol, but also as an effective photocatalyst to degrade dyes with H2 O2 . Due to the bifunctions, reuse of the Ag‐CuO substrate is demonstrated with a light irradiation cleaning process.